Voices of Hope: Leveraging Think-Aloud Cognitive Interviews to Develop a Hope Assessment Tool for Young People Living with Chronic Health Conditions - Emily von Scheven; Mitchell Braun; Bhupinder Nahal; Emily R. Perito; Paul Brakeman; William Daniel Soulsby; Laura Quill; Addison Cuneo; Linda S. Franck (Children)
Background/Objectives: Hope is a universal, multidimensional, and nuanced concept that may have specific meaning for young people living with chronic health conditions anticipated to last into adulthood. We previously identified definitions of hope for youth living with chronic health conditions derived from young people’s and their caregivers’ own words. Here, we aimed to develop a hope assessment tool to facilitate the future evaluation of interventions to support wellness and health for young people growing up with chronic health conditions; Methods: We developed Likert-type scale questions using the young people’s and caregivers’ definitions of hope and applied the think-aloud cognitive interview method to assess understanding and to inform sequential iteration. Interviews were recorded and insights from participant interviews were analyzed thematically. Results: In total, 11 youth (age 12–16 years) with various chronic health conditions completed surveys and interviews over three iteration cycles. Responses to the six-point Likert-scale questions ranged from 1 (none of the time) to 6 (all of the time) (median 5). All of the young people (n = 11) reported that they do things they enjoy, either all of the time or most of the time. In contrast, only 36% felt energetic, either all or most of the time. Three themes were identified: my body and hope; my identity, self-image, and hope; and my world and hope. Conclusions: In addition to gaining important feedback that allowed us to improve item word choice to maximize assessment tool understanding, we gained valuable insights into the multidimensional construct of hope. Thematic analysis revealed the importance of physical symptoms and identity to the meaning of hope in the context of a young person’s life. Our new hope assessment tool derived from the young people’s own definition of hope has face and content validity for use in clinical and research settings to evaluate hope among pediatric patients living with chronic health conditions.